Birowo High Starting Performance DC Motor (Nsc Press, 2015)
Crane or lifting machine is a tool that widely used in the container port at Dermaga Tanjung Perak Surabaya City, with series excited DC motor movement. The main functions of crane are to lift, move and discharge some goods from the origin place to determined place. The main composition of crane is electric motor as driver and gearbox as reduction of gear transmission and controller as the manager of electric motor speed. From three main components above, the component that needs serious treatment is the controller for the series excited dc motor. The stability control system of crane is the starting current at series dc motor. High starting performance dc motor of a crane with volt/hertz control requires rapid dynamics and precise regulation, that make the need of direct control is an urgent demand. Therefore, an independent control of torque and flux, which is similar to a separately excited DC motor is needed. Series DC motor has a high starting torque while separately excited DC motor can operate above the base speed in the starting current. Therefore, in this paper a high starting performance dc motor is suggested to run the series DC motor below base start. The Series DC motor direct control strategy is explained and a control circuit is proposed. A steady-state and transient analysis of the series dc motor is performed below andabove base starting current.